Pelatihan Pembuatan Bioplastik Untuk Peningkatan Kreativitas Siswa Di Sma Nasional Malang - Endah Kusuma Rastini; Siswi Astuti; Fourry Handoko; Prima Vitasari (JASTEN (Jurnal Aplikasi Sains Teknologi Nasional), 2020)
The use of plastic is widely known in everyday life, with a variety of advantages (light but strong, transparent, waterproof, low price). But besides having advantages, conventional plastics also have disadvantages, namely that they are difficult to decompose and pollute the environment when they burn. The need to reduce the use of conventional plastics and replace them with the use of bioplastics in the community is still often socialized, one of which is to students at SMA Nasional Malang. The aim of training and socializing environmentally friendly bioplastics is so that students can reduce the use of conventional plastics and switch to using environmentally friendly products, as well as being able to make bioplastic products. The result of the bioplastic making training is that students are able to make eating and drinking utensils made from bioplastics with various models they like. Through socialization, students began to change their lifestyle by reducing the use of conventional plastics and switching to using environmentally friendly products. To better understand the dangers of conventional plastics to the environment, students compared the biodegradability of conventional plastics and bioplastics. The result is that bioplastics break down faster than conventional plastics. Knowledge of bioplastics and their raw materials is new to them. From the questionnaire, it was found that Malang National Senior High School students were very interested in the training provided, some wanted to make various bioplastic product creations independently and hoped that there would be other training to help students develop their knowledge and creativity.